FACTORS INFLUENCE CHARACTER OF CARING NURSES’ AT HOSPITALS IN GRESIK - Siti Nur Qomariah (UPT Penerbitan Universitas Jember, 2017)
ABSTRACT Background: Caring is importance and essence in nursing which means accountability of relationships between nurses and clients, where nurses help client participation, acquire knowledge and improve client health. The purpose of this study was to explain the various factors that influence the character of caring nurses in all hospital at Gresik City. Methods: This study used cross-sectional design with 85 nurses used cluster sampling in RSUD Ibnu Sina Gresik, Semen Gresik Hospital, Petrokimia Gresik Hospital, and Muhammadiyah Gresik Hospital. Independent variables were psychological factors: intrinsic motivation, extrinsic, personality; Individual factors include ability, skills, age, gender, education, length of work. Organizational factors: nurse unit manager leadership style, income, material resources and model of nursing care wards. The dependent variable was caring character of nurses. Data were collected using questioner and data were analyzed using multiple logistic regression test with significance level α ≤ 0.05. Results: The average value of caring nurse character= 87.19; Most of the respondents were in good category (90.6%). There was influence of psychological factors: intrinsic motivation (p = 0.017) and extrinsic motivation (p= 0.037) with caring character of nurse. There was influence of individual factors: age (p = 0.043), length of work (p = 0.038), income/ month (p= 0.011) with caring. There was no influence of organizational factor with caring character. Conclusions: Character of caring nurses in each hospital can be improved by continuing education and nursing training with considering intrinsic and extrinsic motivation factors of nurses. Keywords: Caring, Nurses, Hospital.